ChemInform Abstract: A Facile Access to Substituted Indoles Utilizing Palladium Catalyzed Annulation under Microwave Enhanced Conditions. Issue 1 (7th January 2014) - Karuvalam, Ranjith P.; Haridas, Karickal R.; Sajith, Ayyiliath M.; Muralidharan, Arayambath
Abstract A microwave promoted Pd‐catalyzed cyclocondensation of o‐iodoanilines with aliphatic aldehydes (I) is developed to give 3‐substituted indoles in good yields.